The Unexpected Power of Mistakes in Language Learning - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
This article challenges the conventional view of mistakes as obstacles in language acquisition, arguing instead that they are crucial stepping stones toward fluency. It explores the cognitive processes underlying error correction, the benefits of embracing mistakes as learning opportunities, and practical strategies for teachers and learners to foster a positive attitude towards errors in the language learning process. The article concludes by emphasizing the importance of creating a psychologically safe learning environment where mistakes are not feared but celebrated as integral components of successful language acquisition.